Assessment of Salinity Tolerance in Lepeophtheirus salmonis Following Five Generations of Freshwater Treatment Selection - Reza Ghanei‐Motlagh; Shona K. Whyte; Manuel Soto‐Dávila; Eyesun Fajei; Maricruz Guevara; Amber F. Garber; Gro Vee; Preben R. Antonsen; Gordon Ritchie; Mark D. Fast (Journal of Fish Diseases, 2026)
Non‐medicinal approaches for controlling sea lice ( Lepeophtheirus salmonis ) infestations, such as freshwater (FW) treatments, have been increasingly implemented to support more sustainable parasite control in aquaculture. This study evaluated the efficacy of FW treatment against sea lice under controlled experimental conditions and assessed the potential development of resistance across multiple generations. Sea lice populations were maintained over five consecutive generations, and FW efficacy was evaluated by quantifying lice abundance on Atlantic salmon before and after treatment. Resistance assessment involved comparative bioassays using copepodid and adult life stages from two distinct populations, one exposed to FW and the other a saltwater (SW) control group. Our results demonstrated that a 4 h FW treatment significantly reduced total lice abundance, while an extended 18‐day exposure resulted in complete detachment of all lice from salmon. Importantly, bioassay comparisons revealed no evidence of resistance development, as both FW‐exposed and SW‐control populations maintained similar susceptibility across generations. The absence of measurable changes in salinity tolerance over multiple generations suggests that FW protocols may remain a viable and sustainable management strategy. However, the potential for genetic or epigenetic variation in FW tolerance among lice populations warrants further investigation to better understand long‐term implications for treatment efficacy.